Chase Moore: capstone - Moore, Chase, artist (Colorado State University. Libraries, 2015)
The artist's statement: My work is primarily concerned with transience. Drawing from history and personal experience, I try to recreate lost moments in time. I am inspired by the idea of travel, both on a personal level and a societal. Drawing from America's history of transculturation, westward expansion, and cultural blending, I attempt to weave in the narrative of my own life which has been largely defined by instability and travel. I use the mediums of drawing and printmaking, focusing primarily on expressive and chaotic line work. Another theme that influences my work is urbanism. I am concerned with the ideas behind architectural styles and the cultural forces they may represent. I also draw incredible inspiration from the built environment.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing; printmaking